Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/molecules28083300
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Class of Acylthiourea-Containing Isoxazoline Insecticides against Plutella xylostella

Abstract: Isoxazoline structures are widely found in natural products and are rich in biological activities. This study discloses the development of a series of novel isoxazoline derivatives by introducing acylthiourea fragments to access insecticidal activity. All synthetic compounds were examined for their insecticidal activity against Plutella xylostella, with results showing moderate to strong activity. Based on this, the structure–activity relationship analysis was carried out via the constructed three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…In addition, studies on the insecticidal activity of isoxazolines reported in recent years have confirmed that isoxazoline compounds can significantly inhibit the GABA receptors of insects. For example, Hu and Song et al revealed that isoxazoline compounds 98 and 99 (Figure ) may affect the insect’s nervous system by acting on the GABA receptors. Our research group also confirmed compound 100 (Figure ) as an inhibitor of insect GABA receptor via proteomics and electrophysiological experiments …”
Section: Mechanism Of Action Of Oxime Insecticidessupporting
confidence: 63%
See 2 more Smart Citations
“…In addition, studies on the insecticidal activity of isoxazolines reported in recent years have confirmed that isoxazoline compounds can significantly inhibit the GABA receptors of insects. For example, Hu and Song et al revealed that isoxazoline compounds 98 and 99 (Figure ) may affect the insect’s nervous system by acting on the GABA receptors. Our research group also confirmed compound 100 (Figure ) as an inhibitor of insect GABA receptor via proteomics and electrophysiological experiments …”
Section: Mechanism Of Action Of Oxime Insecticidessupporting
confidence: 63%
“…The team successfully isolated two enantiomers of compound 99 via high performance liquid chromatography, wherein the cis -configuration exhibited an insecticidal activity that was 44 times higher than that of the trans -configuration. However, the introduction of large groups resulted in a decrease in insecticidal activity of the compound. , In addition, our research group synthesized a series of isoxazoline molecules containing diacylhydrazine based on the core framework of fluralaner. Among them, compound 100 exhibited the LC 50 value of 0.37 μg/mL against P. xylostella and was found to be an inhibitor of GABA receptor in insects via proteomic and electrophysiological experiments .…”
Section: Isoxazoline Derivatives With Insecticidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…86). 138 A series of novel acyl thiourea derivatives (161a-s) was evaluated for their mosquito larvicidal activity against C. quinquefasciatus and A. aegypti 3rd instar larvae. Compound (161l) showed the highest larvicidal activity with LC 50 values of 0.0044 mM and 0.0070 mM, and LC 90 values of 0.0058 mM and 0.0103 mM against C. quinquefasciatus and A. aegypti, respectively.…”
Section: Biological Aspectsmentioning
confidence: 99%
“…WHUA03267 and St. sp. WHUA03072 21 . Additionally, molecular docking was used to assess insecticidal activity against Plutella xylostella and illustrate the identified compound action with the GABA (γ-aminobutyric acid) receptor 21 .…”
Section: Introductionmentioning
confidence: 99%